2014
DOI: 10.1007/s00125-014-3287-8
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes susceptibility gene variants predispose to adult-onset autoimmune diabetes

Abstract: Aims/hypothesis Latent autoimmune diabetes in adults (LADA) is phenotypically a hybrid of type 1 and type 2 diabetes. Genetically LADA is poorly characterised but does share genetic predisposition with type 1 diabetes. We aimed to improve the genetic characterisation of LADA and hypothesised that type 2 diabetes-associated gene variants also predispose to LADA, and that the associations would be strongest in LADA patients with low levels of GAD autoantibodies (GADA). Methods We assessed 41 type 2 diabetes-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 47 publications
6
47
2
Order By: Relevance
“…Conditional analysis in the Danish part of the T2D association data showed an unchanged effect size of rs2650000 on T2D when conditioning on rs7957197 (unconditional OR 0.95, conditional OR 0.96), yet conditional analysis of DIAGRAM data is not available and future studies will be needed to conclude whether rs2650000 and rs7957197 are independent T2D association signals. Recently, rs2650000 was reported to be associated with type 1 diabetes in a small sample from Sweden and Finland (33). Of interest, direction of effect for rs265000 on serum CRP and T2D ( Figure 1) indicates that the effect of HNF1A variation on T2D is not mediated through serum CRP levels which is in line with previous studies of the pleiotropic effects of variants in HNF1A (34).…”
Section: Discussionsupporting
confidence: 62%
“…Conditional analysis in the Danish part of the T2D association data showed an unchanged effect size of rs2650000 on T2D when conditioning on rs7957197 (unconditional OR 0.95, conditional OR 0.96), yet conditional analysis of DIAGRAM data is not available and future studies will be needed to conclude whether rs2650000 and rs7957197 are independent T2D association signals. Recently, rs2650000 was reported to be associated with type 1 diabetes in a small sample from Sweden and Finland (33). Of interest, direction of effect for rs265000 on serum CRP and T2D ( Figure 1) indicates that the effect of HNF1A variation on T2D is not mediated through serum CRP levels which is in line with previous studies of the pleiotropic effects of variants in HNF1A (34).…”
Section: Discussionsupporting
confidence: 62%
“…A very recent study expanded on the TCF7L2 observations by testing all established GWAS-implicated T2D loci in the context of LADA [69]. In addition to TCF7L2, the authors also found strong evidence for the zinc finger, MIZ-type containing 1 (ZMIZ1) locus being associated with the disease.…”
Section: Latent Autoimmune Diabetes In Adultsmentioning
confidence: 91%
“…However, it is becoming increasingly clear that the magnitude of the association between LADA and TCF7L2 is correlated with antibody titer, where the lower it is, the stronger the association [69,81]. Furthermore, it has even been proposed that TCF7L2 genotype status can be used to discriminate between middle-aged antibody-positive patients from those that are young antibody-positive [82].…”
Section: Latent Autoimmune Diabetes In Adultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the association of DM-2 associated Transcription factor 7-like 2 (TCF7L2) and Zinc finger MIZ-type containing 1 (ZMIZ1) risk gene variants with LADA is important and against the arguments denying LADA as a distinct entity; also, the differences in human leukocyte antigen (HLA) haplotypes for both risk and protection complement the idea of LADA as a separate identity [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%